2004
DOI: 10.1111/j.1440-1614.2004.01315.x
|View full text |Cite
|
Sign up to set email alerts
|

Insight and hopelessness in forensic patients with schizophrenia

Abstract: Mean insight scores in patients with schizophrenia with a forensic history do not differ significantly from those in non-forensic populations. Being more aware of being mentally ill may be a risk factor for hopelessness about the future. The limitations of the study are the small sample size, and the fact that it is confined to a relatively clinically stable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 43 publications
(49 reference statements)
2
29
0
1
Order By: Relevance
“…It is obvious that poor insight impacts negatively on the QOL of people with schizophrenia, namely by reducing their hope. 126,128 More recently, Kurtz and Tolman, using the Lack of Judgment and Insight item on the PANSS as a measure of insight into illness, and Subjective QOL (SQOL), which targets subjective satisfaction with one's living situation, work, social contacts and psychological state, confirmed that illness insight was inversely related to SQOL as reported by Aghababian et al using the same design. [129][130][131][132] Similarly, in 1432 schizophrenia patients Mohamed et al found a small but significant correlation between higher insight and lower QOL.…”
Section: Insight and Poor Quality Of Lifesupporting
confidence: 54%
“…It is obvious that poor insight impacts negatively on the QOL of people with schizophrenia, namely by reducing their hope. 126,128 More recently, Kurtz and Tolman, using the Lack of Judgment and Insight item on the PANSS as a measure of insight into illness, and Subjective QOL (SQOL), which targets subjective satisfaction with one's living situation, work, social contacts and psychological state, confirmed that illness insight was inversely related to SQOL as reported by Aghababian et al using the same design. [129][130][131][132] Similarly, in 1432 schizophrenia patients Mohamed et al found a small but significant correlation between higher insight and lower QOL.…”
Section: Insight and Poor Quality Of Lifesupporting
confidence: 54%
“…However, those who did show an improvement in awareness and insight also tended to become depressed (Rathod et al 2005). Van Putten et al (1976) found a negative correlation between grandiosity and insight, depression and anxiety as did Carroll et al (2004) who found higher levels of insight in schizophrenia to be linked to an increased risk of lower mood and suicide. Birchwood et al (2000) observed depression occurring independent of schizophrenic symptoms several months post relapse and proposed that this was due to a the demoralizing impact of disability.…”
Section: Review Of the Evidencementioning
confidence: 98%
“…Paradoxically improved insight has been linked to depression and hopelessness (Carroll et al 2004, Lysaker et al 2007). Mintz et al (2003) in their meta-analysis of 40 (English language) papers determining the direction of the relationship between insight and symptom domains in schizophrenia found a small negative relationship between insight and global negative and positive symptoms and a small positive relationship between insight and depressive symptoms.…”
Section: Review Of the Evidencementioning
confidence: 99%
See 2 more Smart Citations